Differential challenges in salivary gland neoplasms - Živković, Nikola; Kostić, Miloš; Cvetanović, Ana; Jovičić Milentijević, Maja; Spasić, Milan; Petrović, Milica; Trajković, Miloš; Denčić, Tijana; Krtinić, Dane (Archives of Biological Sciences, 2021)
Paper description: Salivary gland tumors are a rare group of neoplasms with a broad and overlapping histological presentation despite their dissimilar biological These tumors are a diagnostic challenge. A correct pathohistological diagnosis is the basis for the further course of treatment. Using values of the Ki67 proliferative index and morphometric analysis, we could divide tumors into benign and malignant with high precision. The obtained cut-off values for the proliferative index and the area and optical density indicate that they can serve as reliable parameters to differentiate between benign and malignant tumors. Abstract: Salivary gland tumors are neoplasms characterized by a high level of pleomorphism and histological overlap. One tumor may contain several cell types; therefore, it is necessary to include immunohistochemical staining, as well as morphometric analysis of tumor cells as prerequisites for an appropriate diagnosis. Our research included 120 tumors, such as pleomorphic adenoma, Warthin tumor, basal cell adenoma, myoepithelioma, adenoid cystic carcinoma, mucoepidermoid carcinoma, salivary duct carcinoma, polymorphous low-grade carcinoma and myoepithelial carcinoma. The aim of the study was to differentiate benign and malignant tumors based on the characteristics of nuclei. The expression of Ki67 and the morphometric nuclear parameters – area, perimeter, Feret diameter, integrated optical density, circularity, and roundness, were analyzed. It was observed that the Ki67 proliferative index was statistically significantly higher in malignant tumors (P<0.001). Adenoid cystic carcinoma exhibited the highest value, whereas the lowest value was exhibited in basal cell adenoma. Morphometric analysis showed statistically significantly increased values of integrated optical density (P<0.001) and nuclear size parameters (P<0.05) in malignant tumors. The determination of the Ki67 proliferative index and morphometric analysis of the integrated optical density and area can differentiate benign from malignant tumors with high precision. The presented values suggest the obtained results as cut-off values.